A metabolic dysfunction in early murine osteoarthritis. Issue 3 (June 1981) - Altman, F P
Abstract : Male mice of the STR/ORT strain spontaneously develop an osteoarthritis lesion in the medial tibial condyle. The appearance of the lesion is age-related and by about 15 months has affected almost all animals. Histochemical studies of lactate dehydrogenase and succinate dehydrogenase activities have shown that a region of inactive chondrocytes appears in the cartilage of these mice before major histological evidence of degeneration. It is suggested that this may be an early metabolic dysfunction, which subsequently leads to matrix breakdown due to the lack of essential enzyme cofactors.